An Isoform of Eukaryotic Initiation Factor 4E from Chrysanthemum morifolium Interacts with Chrysanthemum Virus B Coat Protein - Song, Aiping (Public Library of Science, 2013)
BACKGROUND: Eukaryotic translation initiation factor 4E (eIF4E) plays an important role in plant virus infection as well as the regulation of gene translation. METHODOLOGY/PRINCIPAL FINDINGS: Here, we describe the isolation of a cDNA encoding CmeIF(iso)4E (GenBank accession no. JQ904592), an isoform of eIF4E from chrysanthemum, using RACE PCR. We used the CmeIF(iso)4E cDNA for expression profiling and to analyze the interaction between CmeIF(iso)4E and the Chrysanthemum virus B coat protein (CVBCP). Multiple sequence alignment and phylogenetic tree analysis showed that the sequence similarity of CmeIF(iso)4E with other reported plant eIF(iso)4E sequences varied between 69.12% and 89.18%, indicating that CmeIF(iso)4E belongs to the eIF(iso)4E subfamily of the eIF4E family. CmeIF(iso)4E was present in all chrysanthemum organs, but was particularly abundant in the roots and flowers. Confocal microscopy showed that a transiently transfected CmeIF(iso)4E-GFP fusion protein distributed throughout the whole cell in onion epidermis cells. A yeast two hybrid assay showed CVBCP interacted with CmeIF(iso)4E but not with CmeIF4E. BiFC assay further demonstrated the interaction between CmeIF(iso)4E and CVBCP. Luminescence assay showed that CVBCP increased the RLU of Luc-CVB, suggesting CVBCP might participate in the translation of viral proteins. CONCLUSIONS/SIGNIFICANCE: These results inferred that CmeIF(iso)4E as the cap-binding subunit eIF(iso)4F may be involved in Chrysanthemum Virus B infection in chrysanthemum through its interaction with CVBCP in spatial.